2019
DOI: 10.1186/s40814-019-0534-2
|View full text |Cite
|
Sign up to set email alerts
|

The Frailty Risk Score predicts length of stay and need for rehospitalization after kidney transplantation in a retrospective cohort: a pilot study

Abstract: BackgroundFrailty is a widely used measure in older patients as a predictor of poor outcomes after hospitalization and surgery. There is a growing body of data in kidney transplantation suggesting frailty can predict adverse outcomes. There is interest in using chart review measures of frailty and multimorbidity, as they may be equally predictive as physical measurement. This approach holds promise for patient evaluation, identifying candidates for prehabilitation, and targeting resources towards those anticip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 34 publications
(49 reference statements)
0
23
0
Order By: Relevance
“…Jankovic et al 31 observed that an increased number of non-communicable diseases was significantly associated with a higher utilization of health care services, including general practitioner, inhospitalization and length of stay, in Serbia. However, these studies have not considered the healthcare effects of frailty as described recently 24 , 25 , 32 , and some subjects were middle-aged adults. No studies have investigated the association between cardiometabolic diseases and healthcare utilization after adjusting for frailty.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jankovic et al 31 observed that an increased number of non-communicable diseases was significantly associated with a higher utilization of health care services, including general practitioner, inhospitalization and length of stay, in Serbia. However, these studies have not considered the healthcare effects of frailty as described recently 24 , 25 , 32 , and some subjects were middle-aged adults. No studies have investigated the association between cardiometabolic diseases and healthcare utilization after adjusting for frailty.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is considerable individual variability in healthcare expenditure and utilization in aged populations and current multimorbidity measures have only a modest predictive validity for total healthcare expenditure 23 . Several studies have shown that frailty was associated with higher subsequent total healthcare expenditure and utilization after accounting for multimorbidity 24 , 25 . Hence, timely identification of frailty is important to stratify the healthcare utilization and expenditure among older adults.…”
Section: Introductionmentioning
confidence: 99%
“…Elderly patients are more likely to be comorbid compared to their younger counterparts at the time of kidney transplantation (48.2% in elderly KTRs and 28.9% in young patients) [22], and frailty is also highly prevalent in elderly patients receiving renal replacement therapy. [23] The explanation is furthermore supported by a study suggesting that frailty at the time of kidney transplantationevaluated as unintentional weight loss, weakness, exhaustion, low activity, and slowed walking speedindependently predicts a 60% higher risk of readmission. [24] Finally, our study suggested comparability in the risk of 3-month hospital readmission in KTRs with DBD and DCD donors, regardless of age.…”
Section: Discussionmentioning
confidence: 92%
“…Simpler measures, such as walking speed or the Timed Up and Go Test, do not seem be as good of a predictor of outcomes (44,45). Schaenman et al (46) performed a pilot study evaluating the feasibility and utility of a simple chart review-based Frailty Risk Score (FRS) to predict post-transplant outcomes. Their pilot study demonstrated that the FRS is a feasible approach and the preliminary results suggested that the FRS may be able to predict hospital length of stay and rehospitalization risk after operation (46).…”
Section: How Should Frailty Be Identified In the Potential Kidney Tramentioning
confidence: 99%
“…Schaenman et al (46) performed a pilot study evaluating the feasibility and utility of a simple chart review-based Frailty Risk Score (FRS) to predict post-transplant outcomes. Their pilot study demonstrated that the FRS is a feasible approach and the preliminary results suggested that the FRS may be able to predict hospital length of stay and rehospitalization risk after operation (46). The FRS requires further evaluation before it can be recommended for use in clinical practice.…”
Section: How Should Frailty Be Identified In the Potential Kidney Tramentioning
confidence: 99%